Religious Moderation in Preaching in the Era of Industry 4.0 - Solihin Sari; Enang Hidayat; Surahman (al-Afkar, Journal For Islamic Studies, 2025)
In the context of Industry 4.0, the practice of religious moderation in preaching has emerged as a pivotal necessity. This study explores the ways in which digital technologies are reshaping the landscape of religious discourse and the responsibilities of religious leaders. With the proliferation of social media platforms and online communities, preachers have unprecedented opportunities to convey messages of tolerance, understanding, and inclusivity to diverse audiences. The research highlights the significant role of digital tools in countering extremist ideologies that often find a foothold online. By utilizing innovative communication strategies, religious leaders can engage with followers in meaningful ways, fostering an environment that promotes interfaith dialogue and cooperation. This approach not only strengthens community bonds but also mitigates the risks associated with radicalization. Moreover, the study emphasizes the importance of adaptability in religious teachings to meet the demands of a rapidly changing digital landscape. By integrating modern technology into their preaching methods, religious figures can enhance their outreach and relevance, ensuring that messages of moderation resonate with younger generations. Ultimately, the findings suggest that embracing technological advancements is vital for promoting religious moderation in contemporary society.